Impact of biostimulants to improve the growth of local fennel (Foeniculum vulgare) under salinity stress - Zulfiqar, Iqra; Zahid, Najma Yousaf; Qureshi, Abdul Ahad; Hafiz, Ishfaq Ahmed (Journal of Pure and Applied Agriculture, 2023)
Three biostimulants (seaweed extract, humic acid and vegetable extract) with varying concentrations were examined to evaluate their effect on the growth of local fennel. Seaweed extract with 1.5 g, 3.0 g and 4.5 g L -1 concentrations and humic acid with 1 g, 2 g and 3 g concentrations were applied as foliar spray. While vegetable extract was applied as foliar spray with 0.3%, 0.5% and 0.7% concentrations. Irrigation of saline water having EC = 5.0 dS m-1 was done thrice a week. The experiment was laid out using CRD. The main findings show that humic acid at 3 g L -1 significantly alleviated the negative effects of salinity and stimulated fennel growth. The maximum number of branches (7.667 branches per plant) were recorded in plants treated with 0.7% vegetable extract. Plants treated with 3 g humic acid were peaked (4.9667 g) in dry weight followed by 0.7% vegetable extract (4.7667 g dry weight). Early flowering was observed in plants treated with 4.5 g seaweed extract (109 days) followed by 3.0 g humic acid (113 days), while it was delayed in control (123 days). Maximum fresh weight was gained in plants treated with 3.0 g humic acid (33.83 g) followed by 0.7% vegetable extract (29.467 g fresh weight). Fruit/seed weight was higher in plants treated with 3.0 g humic acid followed by 0.7% vegetable extract. This study signifies that the mode of action of these stimulants should be understood, and their responses may be examined at physiological, biochemical, and molecular levels.